La auditoría interna y su relación con la gestión de la Caja Municipal de Ahorro y Crédito de Arequipa 2018 – 2022 - Vasquez Sangama, John Ahmes (2023)
The reality of the micro financial system in Loreto is complicated despite its importance, specifically the Caja Municipal de Ahorro y Crédito de Arequipa operates in the region and is one of the most important institutions in the development of the department of Loreto, it is considered necessary, useful, and convenient to carry out research related to internal auditing and its influence on the management of the Caja Municipal de Ahorro y Crédito de Arequipa. In this sense, the objective of this research work is to determine the relationship between the internal audit and the management of the Caja Municipal de Ahorro y Créditos de Arequipa, during the period 2018 - 2022. For this, a quantitative methodology of a nature was used. non-experimental and correlational design in which it was found that there is a positive and direct relationship between the Internal Audit and the Caja Municipal de Ahorro y Creditos de Arequipa, during the period 2018 - 2022. This relationship is 76% and is consistent with the results of the research work discussed in the background section. In addition, we found that there is a positive relationship between the Internal Audit with the optimal use of resources, in addition to a positive relationship between the Management of the Municipal Savings and Credit Fund of Arequipa and the performance of the internal control of the institution during the period 2018 - 2022.